Zwei harte Knoten: Todes- und Gerichtsangst im Hebräerbrief - Backhaus, Knut (New Testament studies, 2009)
Hebrews 2.14–15 goes beyond the epistle's cultic symbolism and embeds its image of Christ in a poly-mythic framework, thereby illuminating its existential relevance. Faith enables the believer to see through death in order to cope with fear of death. The author does not reflect explicitly on anxiety about death but integrates it into the Christ drama, thus inspiring his addressees to transform their conceptualization of self and purpose (‘terror management’). Arousing eschatological fear of judgment (6.4–8; 10.26–31; 12.16–17) forms part of the deliberative rhetorical strategy. Immediately subsequent to the warnings, the addressees are guided to the opposite emotion of hope. To postulate a theological perpetuum (exclusion of ‘second repentance’) on the basis of a pathetic temporale would be to miss the emotion-centred guidance of the hearer, the rhetorical truth game, and the pragmatic intention of Hebrews.